Association of Single Nucleotide Polymorphisms in Toll-like Receptors with Acinetobacter baumanii Infectionin a Chinese Population - Lei HE; Maohu LIN; Wensheng FAN; Yunxi LIU; Jijiang SUO; Yubin XING; Ning JIA (Tehran University of Medical Sciences, 2016)
Background: During recent years, infection of Acinetobacter baumanii showed a rapid growth in hospitals and community. Toll-like receptors (TLRs) are the most important pattern recognition receptors, which play a critical role during recognizing invading pathogens by the natural immune system. Our objective was to determine the associations of TLRs polymorphisms with the susceptibility to A. baumanii infection in a Chinese population. Methods: We carried out a case-control study, genotyping 13 polymorphisms of TLR-2, TLR-4, TLR-5 and TLR-9 genes on 423 A. baumanii-infected patients and 385 exposed controls. Thirteen SNPs at the TLR-2 (rs3804099, rs7656411 and rs76112010), TLR-4 (rs1927914, rs10759932 and rs11536889), TLR-5 (rs1341987, rs1640827, rs1861172, rs2241097, rs5744174 and rs17163737) and TLR9 (rs187084) genes were analyzed. SNP genotyping was performed using an improved multiplex ligation detection reaction (iMLDR) technique. Results:  The SNP of TLR-9, rs187084, was related to A. baumanii-infection significantly under recessive model (G/G, to A/A + G/A, P = 0.0064, OR = 0.59, 95% CI = 0.40-0.86) after adjustment with age. Besides, the haplotype GCG of TLR-4 was significantly associated with A. baumanii infection (P = 0.027). Conclusion:  TLR-4 and TLR-9 may be related to the susceptibility to A. baumanii infection in a Chinese population.